The effect of health education on adolescent girls’ knowledge of cyberbullying: A study at Palangka Raya Christian Midlle School - Pristina, Nia; Putri, Berliana Cahyani; Carolina, Meilitha (Institute Of Computer Science (IOCS), 2025)
Cyberbullying can be defined as a form of bullying that utilizes digital technology to intentionally and repeatedly harm others. One effective effort to prevent cyberbullying is through health education, which aims to increase adolescents’ awareness and understanding of this issue. Early prevention plays a critical role in helping teenagers recognize, identify, and respond to cyberbullying behavior. Improved knowledge can enhance adolescents’ concern for their safety both in school and in their surrounding environments. This study aimed to examine the effect of health education on the knowledge of female students about cyberbullying at Palangka Raya Christian Middle School. The research employed a pre-experimental design with a one-group pre-test and post-test approach. A total of 31 female students were selected using total sampling. The results showed a significant increase in students’ knowledge after receiving health education. The Wilcoxon signed-rank test indicated a statistically significant difference, with a p-value of 0.000 (p < 0.05). In conclusion, the study demonstrates that health education has a significant effect on increasing the knowledge of teenage girls about cyberbullying. Preventive strategies such as providing relevant health education can be effective in reducing cyberbullying behavior and fostering a generation of digitally responsible and healthy adolescents.